Lighting Up RNA-Cleaving DNAzymes for Biosensing - Kha Tram; Pushpinder Kanda; Yingfu Li (Journal of Nucleic Acids)
The development of the in vitro selection technique has allowed the isolation of functional nucleic acids, including catalytic DNA molecules (DNAzymes), from random-sequence pools. The first-ever catalytic DNA obtained by this technique in 1994 is a DNAzyme that cleaves RNA. Since then, many other RNase-like DNAzymes have been reported from multiple in vitro selection studies. The discovery of various RNase DNAzymes has in turn stimulated the exploration of these enzymatic species for innovative applications in many different areas of research, including therapeutics, biosensing, and DNA nanotechnology. One particular research topic that has received considerable attention for the past decade is the development of RNase DNAzymes into fluorescent reporters for biosensing applications. This paper provides a concise survey of the most significant achievements within this research topic.